Cyberstalking em relacionamentos íntimos: contribuições de variáveis individuais e sociais - Silva, Paulo Gregório Nascimento da (2023)
This research protocol has the general objective of verifying which personality traits (Big Five and dark) and human values can explain cyberstalking behavior. For that, four studies were proposed, corresponding to four different articles. The first article sought to adapt, gathering psychometric evidence from the Intimate Partner Cyberstalking Scale (IPCS) in a Brazilian context. In two studies (N = 467), the psychometric parameters of the IPCS were evaluated using different techniques (e.g., Confirmatory Factor Analysis, Item Response Theory), in addition to proposing a short version of the scale. Both versions had a reliable one-dimensional structure and had similar correlations with machiavellianism, psychopathy, and narcissism. Second article aimed to adapt the Assessment of Sadistic Personality (ASP) for Brazil, investigating the psychometric qualities of the instrument. Two studies with participants from different Brazilian states have been conducted. Study 1 (N = 242), the ASP was adapted, and an exploratory factor analysis was performed, which suggested a unifactorial structure. Study 2 (N = 225), the confirmatory factor analysis indicated adequate indicators and satisfactory reliability, in addition to athering evidence of convergent validity of ASP with the Dark Triad and the = cyberstalking. Third article certainly verifies the predictive power of personality traits, controlling for the gender variable, in cyberstalking perpetration behaviors. 267 people from different Brazilian states participated (M = 22.83). IPCS, Big Five Personality Factors Inventory and sociodemographic questions were applied. Results assessed, through hierarchical multiple regression, that the neuroticism personality trait explained the perpetration behavior of cyberstalking and that the gender variable did not influence this relationship; however, it demonstrated that people with high levels of emotional instability can exhibit cyberstalking perpetration behaviors. Fourth article aimed know the extent which human values could mediate the relationship between dark personality and the perpetrator behavior of cyberstalking in intimate relationships. 316 people from different Brazilian regions participated (M = 26.92). These are mostly women (57.9%), dating (42.1%) or married (24.1%), who answered the instruments: IPCS, Dark Triad Dirty Dozen, Assessment of Sadistic Personality, the Questionnaire of Basic Values and socio-demographic issues. Correlations and regressions made it possible to test a mediation model, which indicated that personal values were mediators (partial mediation) of the relationship between narcissism and the perpetrator behavior of cyberstalking. Importance of the dark traits of the dark personality (narcissism) in explaining cyberstalking in intimate relationships is reinforced, and it is worth considering the inclusion of personal values (experimentation) to expand the monological network associated with this conduct, aiming to systematically understand its causes and consequences.